The Role of The Demonstration Method in Improving the Effectiveness of Education - Rahmonova Dilrabo Ibrohim qizi (Genius Publishing Group, 2021)
This article discusses the importance of the demonstration method in improving the effectiveness of education, the use of visual aids in the organization of lessons, the views of pedagogical scientists on the demonstration method
Keywords: Method; demonstration method; pedagogical skills; visual aids